Cover Feature: A Visibly Observable, Programmable Supramolecular Logic Platform and Its Application in Smart Thiols Sensing (Chem. Eur. J. 22/2019). Issue 22 (22nd March 2019) - Chen, Jianchi; Yang, Shu; Yang, Chunrong; Li, Jicheng; Huang, Dan; Lin, Xiao; Guo, Chen; Zhou, Qiuju; Yang, Qianfan; Tang, Yalin
Abstract : Molecular computation is increasingly attractive for its programmability. Here, by using some programming factors, a novel supramolecular system that can execute abundant logic functions was built. In addition, the platform has been applied to the sensing of thiols. This method can smartly filter signals in intracellular conditions. This supramolecular‐based platform illustrates not only an incremental advance for the construction of molecular logic systems, but also demonstrates viable applications in thiol analysis. More information can be found in the Full Paper by Q. Yang et al. on page 5691 .